SUBTHRESHOLD MICROPULSE YELLOW LASER VERSUS SUBTHRESHOLD MICROPULSE INFRARED LASER IN CENTER-INVOLVING DIABETIC MACULAR EDEMA. Issue 8 (August 2015) - Vujosevic, Stela; Martini, Ferdinando; Longhin, Evelyn; Convento, Enrica; Cavarzeran, Fabiano; Midena, Edoardo
<x xml:space="preserve">Abstract</x> Background: To evaluate and compare in vivo retinal and choroidal morphologic changes and macular function in patients treated with yellow (Y-MPL) or infrared (IR-MPL) subthreshold micropulse laser in center-involving diabetic macular edema. Methods: Prospective, randomized, single institution, comparative 6-month pilot study of 53 eyes (53 patients with diabetes). Inclusion criteria were previously untreated center-involving diabetic macular edema with central retinal thickness ⩽400 μm (mild diabetic macular edema). Y-MPL or IR-MPL treatment was performed in a standardized pattern, using in both cases the lowest duty cycle (5%). Morphologic outcomes were the visibility of laser spots (on color fundus photographs [COL], fundus autofluorescence, fluorescein angiography, and spectral domain optical coherence tomography), retinal thickness and volume changes, foveal choroidal thickness changes, and integrity and reflectivity of the outer retinal layers. Visual function outcomes were variation in mean 4° and 12° retinal sensitivity and best-corrected visual acuity. Results: Twenty-six eyes were treated with Y-MPL and 27 eyes with IR-MPL. No visible laser spots on the retina were found on COL, fundus autofluorescence, and fluorescein angiography in both treatment groups at 3 months and 6 months of follow-up. Central retinal thickness, macular volume, foveal choroidal thickness, and best-corrected visual acuity were not significantly different at any follow-up visit between the two treatment groups. There were no changes in the integrity of the external limiting membrane or inner segment/outer segment junction in both treatment groups. Mean central 4° retinal sensitivity increased in both treatment groups at 6 months (P = 0.01 and P = 0.04, respectively). Mean central 12° retinal sensitivity increased in the Y-MPL group only (P = 0.047). But, there was no significant difference in mean 4° and 12° retinal sensitivity between the 2 treatment groups at any follow-up visit. Conclusion: No clinically visible or invisible scars in the macula were found after Y-MPL or IR-MPL treatment. Both Y-MPL and IR-MPL with the lowest duty cycle (5%) and fixed power parameters seem to be safe from the morphologic and visual function points of view in mild center-involving diabetic macular edema.